Impact of Globalisation on Higher Education Sector in India - Sharma, Bhawana (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
From ancient time, India has always played a significant role in knowledge development. Many scientists, economists, mathematicians, astronomers have done many researches and inventions for the welfare of society. Indian education system is playing a significant role in world‟s education. As a result, education is becoming a part of Globalisation. The Globalisation of higher education is the process of exchange activities in research and education among various universities and institutions of different countries. Hence, it integrates the functions, activities and purposes of education at international platform by integrating the knowledge in international, intercultural or global dimensions. The major objective of this study is to study the present status of higher education sector in India. Also, this study highlights the impact and challenges in higher education as a result of Globalisation. The data have been collected through secondary sources. The study makes suitable suggestions to establish sustainable competitive advantage in global education market